Schisandrin alleviates the cognitive impairment in rats with Alzheimer’s disease by altering the gut microbiota composition to modulate the levels of endogenous metabolites in the plasma, brain, and feces - Zhang, Chengqin; Zhang, Ying; Zhao, Tiantian; Mou, Tingting; Jing, Wang; Chen, Jian; Hao, Wenqian; Gu, Shuo; Cui, Meirong; Sun, Yue; Wei, Binbin (Frontiers in Pharmacology, 2022)
As one of the primary active compounds isolated from Schisandrae Chinensis Fructus, multiple studies have found that schisandrin has good effects on AD treatment at the cellular and animal levels. However, the oral availability of schisandrin is very low, so the main mechanism of schisandrin exerted its therapeutic effect on AD through oral administration is not yet fully clarified. Here, we speculated that schisandrin may play a therapeutic effect on AD mainly by regulating the imbalance of GM. In our study, behavioral experiments and H&E staining were used to confirm the pharmacological effects of schisandrin on rats with AD. 16S rDNA gene sequencing and feces, plasma, and brain metabolomics techniques were utilized to investigate the therapeutic effects and mechanisms of schisandrin on cognitive impairment on rats with AD systematically. The results showed that schisandrin improved the cognitive impairment and hippocampal cell loss in rats with AD. The UPLC-QTOF/MS-based metabolomics studies of feces, plasma, and brain showed that 44, 96, and 40 potential biomarkers were involved in the treatment mechanism of schisandrin on rats with AD respectively. Schisandrin improved the metabolic imbalance on rats with AD and the metabolite changes mainly affected the primary bile acid biosynthesis, sphingolipid metabolism, glycerophospholipid metabolism, unsaturated fatty acid biosynthesis. Schisandrin can improve the GM structure disorder in rats with AD and increase the abundance of beneficial bacteria in the gut of rats with AD. The predictive metagenomics analysis predicted that altered GM were mainly involved in lipid metabolism, steroid hormone biosynthesis, arachidonic acid metabolism, biosynthesis of unsaturated fatty acids, bacterial invasion of epithelial cells. The spearman correlation analysis predicted that some affected bacteria have a significant statistical correlation with metabolites in various metabolic pathways. Overall, these studies explain the effect of schisandrin on the brain-gut axis on rats with AD rats from the overall metabolic level. And by affecting the composition of the GM community to improve the cognitive impairment of rats with AD may be the main potential therapeutic mechanism of schisandrin.